Interaction of sex chromosome complement, gonadal hormones and neuronal steroid synthesis on the sexual differentiation of mammalian neurons - Cambiasso, Maria Julia (2017)
Female mouse hippocampal and hypothalamic neurons growing in vitro show a faster development of neurites than male mouse neurons. This sex difference in neuritogenesis is determined by higher expression levels of the neuritogenic factor neurogenin 3 in female neurons. Experiments with the four core genotype mouse model, in which XX and XY animals with male gonads and XX and XY animals with female gonads are generated, indicate that higher levels of neurogenin 3 in developing neurons are determined by the presence of the XX chromosome complement. Female XX neurons express higher levels of estrogen receptors than male XY neurons. In female XX neurons, neuronal derived estradiol increases neurogenin 3 expression and neuritogenesis. In contrast, neuronal-derived estradiol is not able to upregulate neurogenin 3 in male XY neurons, resulting in decreased neuritogenesis compared to female neurons. However, exogenous testosterone increases neurogenin 3 expression and neuritogenesis in male XY neurons. These findings suggest that sex differences in neuronal development are determined by the interaction of sex chromosomes, neuronal derived estradiol and gonadal hormones.